Mixing Layer Height Retrievals From MiniMPL Measurements in the Chiang Mai Valley: Implications for Particulate Matter Pollution - Solanki, Raman; Macatangay, Ronald; Sakulsupich, Vichawan; Sonkaew, Thiranan; Mahapatra, Parth Sarathi (Frontiers in Earth Science, 2019)
Urbanized mountain valleys are usually prone to episodes of high concentrations of air pollutants due to the strong interplay between mountain meteorology and synoptic weather conditions. The mountain valley of Chiang Mai is engulfed by air pollutants with particulate matter (PM) concentration remaining above 50 µg m-3 (PM2.5, 24-hour average) during approximately 13 % days every year (mostly during February to April). This study presents the first time continuous measurements of mini- micro pulse LiDAR (MiniMPL) installed on the valley floor of Chiang Mai, providing vertical backscatter profile of aerosols and clouds from April 2017 onwards. This paper analyzes unique dataset of mixing layer (ML) height measurements made during April 2017 to June 2018 with a temporal resolution of 15 minutes. The ML height derived from the backscatter profile measurements are analyzed to understand the annual, monthly and diurnal variations. The ML height depicts distinct diurnal variations for all months of the year, evolving up to < 3.0 km during April to September. From October onwards the ML evolution is gradually inhibited, reducing to < 2.0 km during October to December and < 1.5 km during January to March. The variations in the concentration of PM were found to be partly modulated by the ML variations (Pearson coefficient ≈ −0.50) during dry season (February, March and April), possibly triggering the aerosol-boundary layer feedback mechanism for high concentrations (100 µg m-3) of PM and low ventilation in the valley. The inhibition of ML evolution due to feedback mechanism further escalates the high concentrations of PM, resulting in severe haze conditions on many days during the dry season.